English Language Linguo-Didactic Discourse as a Reflection of Situation in Modern Language Education in Japan (by Material of Terms of “Teacher” Category in Global and Local English-Language Linguo-Didactic Discourse in Japan) - I. G. Atroshchenko (Научный диалог, 2019)
This article is a continuation of the study on linguodidactics discourse, which focuses on the problems of modern language education in Japan. The purpose of this study is to examine the processes of interaction between the global West-oriented and local Japanese English-language linguo-didactic discourse in the educational space of Japan, as well as to identify conflict areas arising in the process of this interaction. The problem of interaction of these discourses is considered by the author on the material of the terms relating to the basic category of linguodidactics, namely to the category “Teacher.” It is assumed that the analysis of terms in this category will determine common areas and differences in interest of the authors of discourses - native speakers and non-native English speakers, as well as identify the key provisions and problems in modern language education in Japan. In this paper, discourse analysis is carried out on the basis of three-aspect analysis of the linguo-didactic term. This method of analysis allows to conduct an interdisciplinary study involving the sphere of discourse analysis, terminology and intercultural communication. Particular attention is paid to the identification and analysis of the key problems of interaction of the discourses under consideration, such as the problem of interaction between a native English teacher and a Japanese English teacher; the problem of professional development of a Japanese teacher; the problem of communicative English language teaching in Japan.